Edible methylcellulose-based films containing fructo-oligosaccharides as vehicles for lactic acid bacteria - Romano, Nelson Gastón (2014)
The goal of this work was to investigate the physicochemical properties of methylcellulose (MC) based films as stabilizers of two strains of lactobacilli: Lactobacillus delbrueckii subsp. bulgaricus CIDCA 333 and Lactobacillus plantarum CIDCA 83114. The incorporation of 3% w/v fructo-oligosaccharides (FOS) into the MC film formulation improved the viability of L. delbrueckii subsp. bulgaricus CIDCA 333 after film preparation. L. plantarum CIDCA 83114 was intrinsically more resistant as no viability loss was observed upon preparation of the films in the absence of FOS. Scanning electronic microscopy images also showed a good incorporation of microorganisms without affecting the homogeneity of the films. FTIR spectroscopy provided structural information about the bacteria-loaded films. Water sorption isotherms showed an impervious behavior at low aw but on exceeding 0.7 of aw the film started to dissolve and form syrup, causing a drastic drop of bacterial viability (log N/N0 ≤ − 5). Dynamic mechanical analysis (DMA) demonstrated that the incorporation of microorganisms into the MC films had no effect on vitreous transition temperatures. FOS incorporated into the MC films had a plasticizing effect. Microorganism-loaded films were stored at relative humidities (RH) ranging from 11 to 75%. Both strains could be stored at 11% RH for 90 days. At 33 and 44% RH L. delbrueckii subsp. bulgaricus CIDCA 333 could be stored up to 15 days and L. plantarum CIDCA 83114 up to 45 days. At 75% RH only L. plantarum CIDCA 83114 could be equilibrated (log N/N0: − 2.05 ± 0.25), but CFU/g films were undetectable after 15 days of storage. The results obtained in this work support the use of MC films containing FOS as a good strategy to immobilize lactic acid bacteria, with potential applications in the development of functional foods.